The urinary excretion of epigenetically modified DNA as a marker of pediatric ALL status and chemotherapy response - Rafal Rozalski; Daniel Gackowski; Aleksandra Skalska-Bugala; Marta Starczak; Agnieszka Siomek-Gorecka; Ewelina Zarakowska; Martyna Modrzejewska; Tomasz Dziaman; Anna Szpila; Kinga Linowiecka; Jolanta Guz; Justyna Szpotan; et al. (Scientific Reports, 2021)
Abstract The active DNA demethylation process may be linked to aberrant methylation and may be involved in leukemogenesis. We investigated the role of epigenetic DNA modifications in childhood acute lymphoblastic leukemia (ALL) diagnostics and therapy monitoring. We analyzed the levels of 5-methyl-2′-deoxycytidine (5-mdC) oxidation products in the cellular DNA and urine of children with ALL (at diagnosis and during chemotherapy, n = 55) using two-dimensional ultra-performance liquid chromatography with tandem mass spectrometry (2D UPLC–MS/MS). Moreover, the expression of Ten Eleven Translocation enzymes (TETs) at the mRNA and protein levels was determined. Additionally, the ascorbate level in the blood plasma was analyzed. Before treatment, the ALL patients had profoundly higher levels of the analyzed modified DNA in their urine than the controls. After chemotherapy, we observed a statistically significant decrease in active demethylation products in urine, with a final level similar to the level characteristic of healthy children. The level of 5-hmdC in the DNA of the leukocytes in blood of the patient group was significantly lower than that of the control group. Our data suggest that urinary excretion of epigenetic DNA modification may be a marker of pediatric ALL status and a reliable marker of chemotherapy response.